A meta-analysis of microRNA-17 as a potential biomarker in diagnosis of colorectal cancer - Liu, Tao; Yin, Libin; Yan, Guoqiang; Li, Chao; Wang, Lei (Cellular and Molecular Biology, 2018)
This meta-analysis was aimed to determine the diagnostic accuracy of circulating microRNA-17 for colorectal Cancer (CRC). Databases including PubMed, Embase, Web of Science, Cochrane Library and China National Knowledge Infrastructure (CNKI) were searched up to February 23, 2018 for eligible studies. Quality Assessment of Diagnostic Accuracy Studies (QUADAS) was employed to assess the quality of the included studies. Meta-analysis was performed in STATA 13.0. Ten studies with total 938 CRC patients and 638 control individuals were included in this meta-analysis. All of the included studies are of high quality. The summary estimates revealed that the pooled sensitivity is 0.75 (95% confidence interval (CI): 0.60–0.85) and the specificity is 68% (95% CI: 0.56–0.77), for the diagnosis of CRC. In addition, the area under the summary ROC curve (AUC) is 0.76. The current evidence suggests that circulating miR-17 has the potential diagnostic value for CRC. More prospective studies on the diagnostic value of circulating miR-17 for CRC are needed in the future. Together, microRNA-17 might be a novel potential biomarker in the diagnosis of colorectal cancer, and more studies are needed to highlight the theoretical strengths.